Study of the trapezius muscle region pressure pain threshold and latency time in young people with and without depressed scapula. Issue 1 (February 2015) - Lee, Kuan-Ting; Chuang, Chiung-Cheng; Lai, Chien-Hung; Ye, Jing-Jhao; Wu, Chien-Lung
Abstract The scapula is stabilized in or moved to a certain position to coordinate shoulder function and achieve shoulder and arm movement during the athletic and daily activities. An alteration in the scapular position both at rest and during arm movements is commonly associated with shoulder injury or dysfunction. The purpose of this study was to assess the influence of the depressed scapular position using pressure pain threshold (PPT) and delayed muscle activation of the upper and middle trapezius muscles. The study included 20 subjects who were divided into normal shoulder (n = 12) and depressed shoulder (n = 8) group. PPT was measured in a relaxed position. Muscle activity was recorded using surface electromyography and by calculating each shrug's muscle latency time (MLT). The results revealed that the healthy young subjects with depressed scapular position had signiﬁcantly lower PPT levels than those with normal scapular position both in the upper and middle trapezius muscle (P < 0.05). MLT of the upper trapezius was significantly delayed in both sides during the shoulder shrugs (P < 0.05).